Inclusão no ensino de física: o ensino das qualidades fisiológicas do som para alunos surdos e ouvintes - Castro, Jederson Willian Pereira de (2015)
This research was conducted in a regular school in a city of Minas Gerais state which receives deaf students from the 6th year of secondary school to the 3rd year of high school. Our goal was to promote the learning of sound and its qualities in an inclusive way for all students. In order to reach this goal, a methodological sequence was built with the use of Assistive Technology and specific didactic support material was developed for deaf students, by using the theories of Ausubel’s meaningful learning and the social interaction of Vygotsky. Assistive technology was used to enable deaf students to comprehend the sound and its qualities through touch of a loudspeaker and the eyesight through the graphical representation of sound by the Visual Analyser and Audacity programs. The didactic support material was translated and signaled in LIBRAS (Brazilian Sign Language) and it will enable deaf students to study the sound and its qualities by themselves. The construction of this material was in Portuguese, therefore it was translated by an LIBRAS interpreter, which every word is replaced by signs. The results showed the importance of use of specific resources in the process of their inclusion. It was concluded that deaf students can also have a significant learning about sound and their inclusion can also benefit students can hear.